Development of A Sustainable Transportation System and Autonomous Mobility in Majalengka - Kamaludin; Muhamad Taufik; Yusra Aulia Sari (Fakultas Teknik Sipil dan Perencanaan, 2025)
This research carries out an in-depth investigation into the potential for developing a sustainable and autonomous transportation system in the Majalengka area experiencing rapid urbanisation and using survey and interview methods. This research analyses the current transportation conditions and community readiness for autonomous mobility and identifies existing obstacles and opportunities. Research findings show a high dependence on private vehicles and pressing environmental problems. Based on these findings, this research formulates several strategic recommendations to encourage the implementation of mobility and autonomy, including infrastructure investigations, preparation of regulations, and socialisation campaigns.